2005
DOI: 10.1002/humu.20227
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 65 tuberous sclerosis complex (TSC) patients byTSC2DGGE,TSC1/TSC2MLPA, andTSC1long-range PCR sequencing, and report of 28 novel mutations

Abstract: Tuberous sclerosis complex (TSC) is a severe autosomal-dominant disorder characterized by the development of benign tumors (hamartomas) in many organs. It can lead to intellectual handicap, epilepsy, autism, and renal or heart failure. An inactivating mutation in either of two tumor-suppressor genes-TSC1 and TSC2-is the cause of this syndrome, with TSC2 mutations accounting for 80-90% of all mutations. Molecular diagnosis of TSC is challenging, since TSC1 and TSC2 consist of 21 and 41 coding exons, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 42 publications
3
21
1
1
Order By: Relevance
“…In addition, mutations in the genes that encode other regulatory components of the mTOR pathway, eg, TBC1D7 and Rheb , have not been associated with TSC, ie, there is no known TSC3 gene. Mutations in TSC1 are often small insertions or deletions (indels) that result in shortened (truncated) protein, whereas TSC2 mutations include large deletions, indels, nonsense, and missense mutations 14,15. Splicing errors account for a small number of TSC1 and TSC2 mutations.…”
Section: Tsc Geneticsmentioning
confidence: 99%
“…In addition, mutations in the genes that encode other regulatory components of the mTOR pathway, eg, TBC1D7 and Rheb , have not been associated with TSC, ie, there is no known TSC3 gene. Mutations in TSC1 are often small insertions or deletions (indels) that result in shortened (truncated) protein, whereas TSC2 mutations include large deletions, indels, nonsense, and missense mutations 14,15. Splicing errors account for a small number of TSC1 and TSC2 mutations.…”
Section: Tsc Geneticsmentioning
confidence: 99%
“…This mutation has been reported in several patients. 17,18,[45][46][47][48] In conclusion, we describe two patients with TSC who presented with unusually large and disfiguring facial angiofibromas. We suggest that localized lymphedema contributes to the appearance of these lesions.…”
Section: Discussionmentioning
confidence: 71%
“…A disease-associated mutation of the catalytic residue, N1643I [90,91], rendered TSC2 1525-1742 inactive, as expected, as did two other proximal mutations (H1640Y [92] and K1638N [91]). Among disease-associated mutations predicted to be located on the same face of the GAP domain as the catalytic residue, we found that the charge perturbing mutation E1558K [89,93] eliminated GAP activity and the conservative L1594M substitution [88] reduced GAP activity by approximately 80%, whereas the D1690Y mutation [94] did not impair GAP activity of TSC2 1525-1742 , despite its association with tuberous sclerosis disease. We were also able to show that a TSC2 polymorphic variant (D1636N) found in a TSC patient carrying an additional mutation [95] had no direct effect on GAP activity.…”
Section: Rheb and Tsc2gapmentioning
confidence: 86%